Să luăm dreptul transnațional (public) în serios!// Taking (Public) Transnational Law Seriously! - Radu Bogdan Bobei (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice, 2022)
We have been accustomed with the idea that the making of international law is the „business” of the nation-States only. The idea of a State-centric international law inspired the realities of the XXth centrury. At the time of drafting this paper, I note that international law became the „business” of the private actors as well. International society amounts to become truly a transnational law. In the process of its making, international law amounts to become a true transnational law. The so-called methodology of „transnational law” invites us all to take (public) transnational law seriously!